Making sweatshops : the globalization of the U.S. apparel industry - Rosen, Ellen Israel (University of California Press, 2002)
A comprehensive historical analysis of the globalization of the US apparel industry, this book focuses on the re-emergence of sweatshops in the United States and the growth of the phenomenon abroad.